THE EFFECT OF WORD FIND PUZZLE ON THE STUDENTS’ VOCABULARY MASTERY - Syaukani Syaukani; Intan Zulfira Pane (VISION, 2020)
The research was intended to know the effectiveness of Word FindPuzzle in the students’ vocabulary mastery which was observed andanalyzed from students of tenth grade at SMA Baitul Aziz BandarKlippa. The method used was quatitative research by using theexperimental research design. The population of this study wastenth grade students of SMA Baitul Aziz Bandar Klippa. In takingthe sample of this research, the researchers took some students ineach classes as the sample used and divided into 2 classes,experimental and control. There were 34 students in theexperimental and 26 students in control. The researchers taught byusing the Word Find Puzzle in the experimental class and taught byusing lecturing method in control class.The researchers used pretest,treatment, and post-test. In control class the score increase59,23 between pre-test and post-test, but in experimental class thescore increase about 68,85. By calculated by used SPSS V24, Theresearcherss concluded that there was a significant effect of theapplication of the Word Find Puzzle learning approach on learningoutcomes, it can be seen from the results of the analysis that this isindicated by the results of hypothesis testing which indicate that theSig. (2 - tailed) <0.05 (0.000 <0.05) and the value of t_ (count)> ttable (6.365> 1.992). Then in post test the researchers found thatthe value of Sig. (2tailed) is 0,923. It is bigger than 0,05(0,923>0,05) Sig. in T-Test (2tailed) is 0,002. It was less than 0,05(0,002>0,05), so there was a significant different between theexperiment class and control class. In other words, the students’achievement in vocabulary mastery is more effective by using WordFind Puzzle than lecturing method.